2017
DOI: 10.1038/s41467-017-00487-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards designer organelles by subverting the peroxisomal import pathway

Abstract: The development of ‘designer’ organelles could be a key strategy to enable foreign pathways to be efficiently controlled within eukaryotic biotechnology. A fundamental component of any such system will be the implementation of a bespoke protein import pathway that can selectively deliver constituent proteins to the new compartment in the presence of existing endogenous trafficking systems. Here we show that the protein–protein interactions that control the peroxisomal protein import pathway can be manipulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Recent reports have explored the localization of engineered proteins to eukaryotic compartments such as the peroxisome 21,22 , mitochondria 19 , and vacuoles 30 . While peer-reviewed) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have explored the localization of engineered proteins to eukaryotic compartments such as the peroxisome 21,22 , mitochondria 19 , and vacuoles 30 . While peer-reviewed) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to approaches that leverage existing organelles [19][20][21][22] , encapsulins have the advantage of being completely orthogonal to endogenous eukaryotic compartments. There is also ample choice of different encapsulin protein variants derived from different families of bacteria and archaea.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the existing peroxisomal protein import system can increase its efficiency for importing enzymes (DeLoache et al, 2016). However, the recent creation of a different protein import system that runs in parallel with the endogenous system provides a step toward synthetic peroxisomes (Cross et al, 2017). Deeper understanding of proliferation mechanisms and the protein-protein interactions that hold the peroxisomal matrix together will also assist in reaching this goal.…”
Section: Synthetic Organellesmentioning
confidence: 99%
“…In another case, it has been reported that protein denominated TGBp1 (triple gene block protein 1) from the pepino mosaic virus can interact with catalase to increase its activity and trigger virus accumulation (Mathioudakis et al ). Moreover, the peroxisomal import system has started to be used as a strategy model to generate designed peroxisomes with a protein composition on demand (Cross et al ).…”
Section: Introductionmentioning
confidence: 99%